Mobilizing the experiential knowledge of an expert elite coach in Modern Pentathlon to propose a framework of intelligibility to "uncertainty of the combat sports` competitor" - Couckuyt, S.; Robin, J.-F.; Sarremejane, P. (Revista de Artes Marciales Asiaticas, 2016)
In previous communications (Couckuyt, Robin, & Sarremejane, 2014, 2015, 2016) and in articles for coaches (Couckuyt, 2016a, 2016b) as part of our thesis on knowledge capitalization we highlighted the interest of knowledge of high-level expert coaches for the coaching community. In this communication, the data collected from a modern pentathlon coach are used to provide a framework of intelligibility of the uncertainty faced by the fighter/competitor, especiall in Kickboxing Light Contact.